FAKTOR-FAKTOR PERSONALITAS DAN SOSIOKULTURAL DALAM PEMBELAJARAN BAHASA KELAS V DI MI AL KIFAYAH PEKANBARU - Nursalim; Abdullah Taufik Ritonga; Marwan; Asmardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of personality and sociocultural factors on language learning among fifth-grade students at MI Al-Kifayah Pekanbaru. Employing a qualitative approach through literature review, this research examines relevant literature to understand how aspects such as motivation, self-confidence, and students' cultural and social backgrounds affect the language learning process. The findings indicate that personality factors, including motivation and self-confidence, play a crucial role in enhancing student participation and the effectiveness of language learning. Meanwhile, sociocultural factors, such as family environment and community, contribute to shaping students' attitudes and language proficiency. Integrating these two factors into learning strategies can create a more inclusive and responsive learning environment tailored to individual student needs, thereby supporting the achievement of optimal language competencies.